Blue laser diode annealing-enhanced bottom-gate low-temperature Poly-Si thin-film transistors. (December 2022) - Xu, Hongyuan; Wang, Xu; Hu, Daobing; Zheng, Feng; Xiao, Juncheng; Lu, Lei; Zhang, Shengdong
Abstract: The low-temperature poly-Si (LTPS) thin-film transistor (TFT) with bottom-gate architecture was successfully developed using the blue laser diode annealing (BLDA) technology. The amorphous silicon (a-Si) was successfully recrystallized by BLDA into LTPS with grain sizes ranging from 0.1 μm to 0.3 μm. With the proper pre-dehydration treatment of a-Si and optimized BLDA conditions, the bottom-gate LTPS TFTs achieved superior performance than a-Si TFTs, including a mobility up to 15.87 cm 2 /Vs. Moreover, such BLDA-enabled bottom-gate LTPS TFT is fully compatible with the incumbent a-Si production line, thus providing a new cost-efficient technology for large-area electronics.